A finite-element based mesh morphing approach for surface meshes. (May 2022) - Claus, Felix; Hamann, Bernd; Hagen, Hans
Abstract: We present a finite element (FE) approach that deforms a given meshed CAD-based simulation model to a shape represented by a triangulation. We use an FE solver to calculate a smooth deformation field that we apply to the simulation mesh. The FE load case derives displacement boundaries from computed distance estimates between source and target meshes. We reduce mesh distortions via an iterative approach until a specified required mesh quality threshold is achieved. Our specific application is concerned with meshes used for sheet metal simulations arising in automotive applications where one wants to construct digital twins of measured sheet metal parts or entire assemblies. The approach is validated for parts and assemblies, considering simulation as well as experimental data. Our computational experiments produce errors below ± 0.05 mm, which is on the order of measurement uncertainty of common optical measurement devices. We provide test results for fully and partially measured parts to document the robustness of our implementation. Highlights: Iterative FE simulation-based mesh morphing algorithm. Handling complex geometries, measurement errors, and partially measured geometries. Validations with simulation and experimental data, with errors below ±0.05 mm. Easy to implement algorithmic scheme for commercial FE simulation software.